Pengaruh pembiasaan belajar dengan metode sosiodrama berbasis role playing terhadap minat membaca dan hasil belajar siswa pada materi memahami lambing burung garuda di SMK Tirta Jaya depok - Dewa mahardika Ardani; Muhammad Abduh; Sri Rumiati (IKRAITH-EKONOMIKA, 2026)
The purpose of this study was to determine the influence of study habits and interest on learning outcomes in Civics, focusing on understanding logos of the Garuda bird. The subject was grade 11 students at SMK Tirta Jaya Depok. The research method used a quantitative survey technique, with a sample of 60 grade 11 students. Data collection used a questionnaire. Data analysis used descriptive statistics, coefficients, multiple correlations, and Peaseson coefficients. Determination and Regression Analysis. Statistical tests used the T-test and F-test. The results of the study were Y = 79.661 - 3.02 X 0.10 X 2 To = -2.378 0.747. From this equation, it shows that every one-unit increase in study habits will decrease the learning outcomes of Civics subjects by 3.02, and vice versa, every one-unit increase in reading interest will increase learning achievements in Civics subjects by 0.10. Then, together, it shows that the study habits variable and the reading interest outcome variable can determine the increase in Civics learning outcomes by 7.8% and are not significant (R2 determination equals 0.330 with an F-test value of 1.170). In addition, the hypothesis testing also shows that there is an influence of study habits on Civics learning outcomes and there is no influence of reading interest on Civics results.